CLASSIFICATION OF WWII TANKS AND VEHICLES IMAGES FROM CONVOLUTIONAL NEURAL NETWORKS (Revista de Estudos Multidisciplinares UNDB, 2023)
This paper describes an analysis of the application and development of a Convolutional Neural Network (CNN) applied in the binary classification of World War II vehicle images, allowing the evaluation of the applied concepts, project feasibility and results obtained. Using a grayscale image base, with about 122 training images for the CNN and 15 images for validation, it was possible to identify an average hit rate of 86.666% among the tests performed, demonstrating that it is It is possible to use a CNN to classify images of WWII vehicles automatically with an acceptable degree of accuracy.
Keywords: Neural networks; Classification; Vehicles; Second World War